Resiliensi pada mantan pecandu NAPZA: Bagaimana peranan dukungan sosial? - Roza Agustin; Herlan Pratikto; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between social support and resilience in former drug addicts. This research is a type of quantitative research using correlational research. The subjects of this study were 115 former drug addicts. The mode of data collection is carried out by distributing questionnaires online using a Google Form using a Likert scale. Based on the results of research using the Sperman-Rho technique, the result is 0.395 with a significance of 0.000 and has a unidirectional connection and a positive value. This means that the higher the social support received, the higher the resilience obtained, and vice versa if the lower the social support received, the lower the resilience received. Keyword: Social Support, former addict, Napza Resilience